Noninfectious Colitides - Bayasi, Mohammed; Quiogue, Jose (Clinics in Colon and Rectal Surgery, 2015)
There are numerous etiologic and pathogenic mechanisms associated with colitis, ranging from infectious to noninfectious colitis. However, despite their different causes, their presentations are often similar making it difficult to formulate the correct diagnosis. This article describes the presentation, endoscopic and pathological findings of six different noninfectious colitides: diversion colitis, neutropenic enterocolitis, disinfectant colitis, corrosive colitis, nonsteroidal anti-inflammatory drug and salicylate-induced colitis, and toxic epidermal necrolysis. In addition, this article discusses the management and current treatment options for these six colitides.
Keywords: diversion colitis; neutropenic enterocolitis; disinfectant colitis; corrosive colitis; salicylate-induced colitis; toxic epidermal necrolysis